Process of Adaptation and Validation of CAPE-V Statements into Spanish and Catalan: A Model for Future Linguistic Adaptations - Calaf, Neus (Revista de Investigación en Logopedia, 2025)
Auditory-perceptual evaluation is essential for diagnosing voice disorders, although its subjectivity poses challenges. The CAPE-V, designed to standardize the assessment of voice qualities, has been adapted to several languages to address these difficulties. One of the main challenges in the cultural and linguistic adaptation of the CAPE-V is modifying the six sentences in Task 2 of the voice sample collection protocol. The aim of this study is to detail the process of linguistic and cultural adaptation of the CAPE-V sentences in its bilingual Spanish/Catalan version, highlighting the decisions made to ensure their applicability in both languages. This study was conducted in several phases, involving three phonetics experts, three voicespecialized speech-language pathologists, and 64 students. Multiple preliminary versions were reviewed through interviews and a pilot test. The sentences were adjusted based on functionality, relevance, and appropriateness, leading to a final version refined through a collaborative review process. The adapted sentences were found to be adequate for evaluating the criteria established by the original instrument: all vowel sounds, the transitions from voiceless to voiced sounds, the ability to maintain glottal vibration, hard glottal attacks, nasal resonance, and intraoral pressure in both languages. The adaptation of the CAPE-V sentences into Spanish and Catalan has preserved the original functionality, ensuring their linguistic relevance. This rigorous and collaborative process can serve as a guide for future cultural and linguistic adaptations of phonetics-dependent assessment tools.
Keywords: Auditory-perceptual evaluation; Voice quality; Voice disorders; CAPE-V; Cultural and linguistic adaptation